Formaldehyde sensing using ZnO nanorods coated glass integrated with microfiber - Jali, Mohd Hafiz; Rahim, Hazli Rafis Abdul; Johari, Md Ashadi Md; Yusof, Haziezol Helmi Mohd; Rahman, B.M.A; Harun, Sulaiman Wadi; Yasin, Moh (Elsevier, 2019)
A proposed formaldehyde (CH2O) sensor is fabricated by exploiting evanescent wave on a glass surface coated with Zinc Oxide (ZnO) nanorods integrated with microfiber. The diameter of silica fiber is reduced by tapering using flame brushing technique to a waist diameter of 6 µm. The glass surface was coated with ZnO nanorods using hydrothermal synthesis method. A significant response to formaldehyde concentrations from 0 ppm to 0.18 ppm was observed due to strong chemisorption process and changeable refractive index of the ZnO nanorods coated glass surface. Thus, the output power of the proposed sensor has reduced linearly from −22.64 dBm to −24.24 dBm with sensitivity and resolution of 9.78 dBm/ppm and 0.0016 ppm respectively. Sensitivity improved by a factor of 3 and the resolution by a factor of 2.5 when the glass surface is coated as compared to uncoated glass surface. The proposed formaldehyde sensor exploit the distinctive features of strong evanescent wave from silica microfiber and surface absorption capability of ZnO nanorods coated glass surface which eased the handling procedure during the synthesis process and sensing applications. Based on the experimental result, the proposed sensor has demonstrated an excellent sensing performance as a formaldehyde sensor. © 2019 Elsevier Ltd